PELATIHAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN BAHASA INGGRIS DI MI NURUL HUDA SEMARUM - Huda, Moh. Choirul; Roistika, Nia (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This program aimed to enhance the digital competence of elementary school teachers through training on the use of digital technology in English language teaching. The training was conducted at MI Nurul Huda Semarum on July 24–26, 2025, involving six teachers as participants. The activity adopted an andragogical, hands-on training approach consisting of orientation, demonstration, simulation, and evaluation stages. The applications introduced were Wordwall, Wayground, and Duolingo. The results showed a significant improvement in participants’ understanding and digital skills, with an average increase of 38% between the pre-test and post-test scores. The average score for the participants’ digital media projects was 21.2 (categorized as Good–Excellent), and the satisfaction survey revealed an average score of 4.6 out of 5 (Very Satisfied). Participants demonstrated high enthusiasm and were able to create interactive teaching materials independently. Overall, the program effectively improved teachers’ ability to integrate digital technology into English language learning in a more interactive and contextual manner.